Coping Strategies in Mothers of Children with Autism: Insight from F-COPES - Musayaroh, Siti; Abadi, Reza Febri; Muslihah, Muslihah; Jannah, Anna Miftahul; Karina, Rr Farhana Rizqi; Maslahah, Sayidatul (Journal of ICSAR, 2024)
Parenting children with autism triggers stress for parents, especially mothers. Every mother needs to have coping strategies to overcome the stress experienced during parenting. This study aims to examine coping strategies in mothers of children with autism. A total of 50 mothers of children with autism participated in this research by filling out the F-COPES scale questionnaire, which consists of 5 subscales: acquiring social support, reframing, seeking spiritual support, mobilizing family support, and passive appraisal. Data was analyzed using Pearson Correlation analysis and Multiple Regression Analysis. The results show that the F-COPES scores of mothers of children with autism are in the moderate category. Reframing, seeking spiritual support, and mobilizing family support are three coping strategies that are most commonly used. Age and number of autistic symptoms in children influence the level of coping strategies of mothers of autistic children. The older the autistic child, the better the mother's coping strategies. Conversely, the more autistic symptoms a child has, the lower the coping strategies the mother has.